2018
DOI: 10.1016/j.toxlet.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic approaches and novel alternatives for organophosphate toxicity

Abstract: Organophosphate compounds (OPCs) are commonly used as pesticides and were developed as nerve agents for chemical warfare. Exposure to OPCs results in toxicity due to their covalent binding and inhibition of acetylcholinesterase (AChE). Treatment for toxicity due to OPC exposure has been largely focused on the reactivation of AChE by oxime-based compounds via direct nucleophilic attack on the phosphorous center. However, due to the disadvantages to existing oxime-based reactivators for treatment of OPC poisonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…[160] pletely recovered the activity of the enzyme up to the level of the positive controla nd the other two reached 60-70%.T hese results are in good agreement with an umber of studies which found that Mannich bases are reactivators of OP-inhibited AChE. [91,113,114,116] While the kinetic assays confirmed recovery of the native enzyme,b ottom-up proteomics were conducted to try and isolate the enzyme in the native, inhibited (re-alkylated), and aged states. As olution of the lead compound 103 wasi ncubated with aged eeAChE for 11 days beforeb eing digested with trypsin.…”
Section: Mannich Bases For the Alkylation Of Aged Acetylcholinesterasesupporting
confidence: 79%
See 4 more Smart Citations
“…[160] pletely recovered the activity of the enzyme up to the level of the positive controla nd the other two reached 60-70%.T hese results are in good agreement with an umber of studies which found that Mannich bases are reactivators of OP-inhibited AChE. [91,113,114,116] While the kinetic assays confirmed recovery of the native enzyme,b ottom-up proteomics were conducted to try and isolate the enzyme in the native, inhibited (re-alkylated), and aged states. As olution of the lead compound 103 wasi ncubated with aged eeAChE for 11 days beforeb eing digested with trypsin.…”
Section: Mannich Bases For the Alkylation Of Aged Acetylcholinesterasesupporting
confidence: 79%
“…Along with testing their non-oxime reactivators with AChE, Stojanovic and co-workers testedt he same library of compoundsw ith paraoxon-inhibitedB ChE. [91] Indeed,s omeo ft he Figure 30. Imidazolium-based oximes for the reactivation of OP-inhibited BChE.…”
Section: Recent Results For Reactivation Of Butyrylcholinesterasementioning
confidence: 99%
See 3 more Smart Citations